Analysis of Mining Taxation in South Africa - Shikwambana, Callous (University of the Witwatersrand, Johannesburg, 2011)
Mining is one of the principal industries in the South African economy, and thus fulfils an important role from the perspective of the fiscus. Mining is a high-level risk investment which involves massive capital expenditure as well as prolonged periods of non-production of mining income. It is because of this that mining taxation receives special treatment. The term ‘mineral’ is central to determining whether or not a taxpayer can be regarded as being carrying on mining operations in South Africa. A mining process usually involves different stages before minerals are obtained, being prospecting and pre-production stages, followed by the production and post-production stages. Income is earned and expenditure is incurred in all the different stages in the life of a mine. The research report will critically evaluate what is meant by ‘mining and mining operations’ as defined in the Income Tax Act 58 of 1962 (‘the Act’). The research report concludes with an analysis and evaluation of how income earned and expenditure incurred in the different stages in the life of a mine are treated in determining the taxable income in respect of a mining taxpayer.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation), to the Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2011.
Keywords: Mineral; Mining operation and Mining; Mining income; Mining expenditure; Contract Mining; Prospecting; Mining rights; Assessed losses; Shaftsinking; Full Annual Redemption; Partial Annual Redemption; Capital expenditure incurred; Recoupment; Environmental Rehabilitation Trust; UCTD; N/A